The Resistance of Javanese and Sundanese Cultural Identities in Indonesian Magical-Realism Novel into English - Nadia Khumairo Ma'shumah; Sajarwa Sajarwa (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2022)
Identity is also at the core of the translation project. Thus, the translator's role as a mediator between different languages and cultures cannot be isolated from efforts to harmonize the building of identity and cultural knowledge. This study investigates how the translator preserves the source text's cultural identity in the target text, based on evidence that the translation process is likewise a cultural transfer. The frameworks for this study were Venuti's idea of